Trends in green accounting research: A systematic literature review - Chairia Chairia; Suci Cahyati; Muhammad Al Fauzan (International Journal of Applied Finance and Business Studies, 2026)
A global issue and problem that is widely discussed by classrooms around the world as well as the mass media is the issue of the environment. Current global environmental issues include climate change, environmental pollution, and over-exploitation of nature. Green accounting is considered more appropriate because it is more fundamental, as it is based on the three basic principles of corporate responsibility, namely economic responsibility (profit), social responsibility (people), and environmental responsibility (planet). The method used in this research is a literature study. Systematic literature study as a literature study research to define systematically, explicitly, and comprehensively a problem topic to identify research gaps and describe research that has been carried out in the past both from the subject and object of research, research methods, and research results. The results is green accounting research has become a relevant research trend in the current conditions aimed at sustainable environmental management including environmental accounting. The topics are interrelated and interconnected, for example, the close relationship between good corporate governance to increase company value and attract investors.